STRATEGI KERJASAMA SISTER CITY KOTA BANDUNG DENGAN PETALING JAYA DI BIDANG EKONOMI PERDAGANGAN - Gia Anggia; Titin Rohayatin; Lukman Munawar Fauzi (Jurnal Caraka Prabu, 2020)
The City of Bandung and Petaling Jaya have collaborated with Sister City in the trade economy sector starting from 2012 and continuing in 2015. MSMEs in Bandung still have many problems running their business and MSMEs are still having difficulty developing. Descriptive research with a qualitative approach. Techniques based on primary data (interviews and observations), as well as secondary data (literature study). The results of the research on the collaboration strategy of Sister City Bandung City with Petaling Jaya in the economic sector can be said to be not optimal. This can be seen, the lack of awareness of the apparatus' resources towards mastery of English, the apparatus has not realized that language acquisition can improve the quality of employee performance in a collaboration strategy between Sister City and Petaling Jaya in the trade economy sector in the field of MSME products in Bandung City. The two Bandung City Governments do not have a specific strategy to overcome the threats associated with Sister City with Petaling Jaya in the trade economy, the three strategies of cooperation through promotional activities in Petaling Jaya.